Analisis Rencana Anggaran Biaya Menggunakan Konsep BIM 5D Pada Pekerjaan Struktur Proyek Villa Jalan Mulawarman Batakan Village Balikpapan - Fatchurrochman, Muhammad Aljabbaaru; Hendriyani, Irna; Pratiwi, Reno (Jurnal Teknologi Terpadu, 2024)
The development of construction technology is currently experiencing rapid progress, with many software programs in the construction field based on the concept of Building Information Modeling (BIM). Among the seven aspects of BIM, one aspect in construction planning is cost estimation planning, also known as BIM 5D. This study aims to analyze the application of the BIM 5D concept using Autodesk Revit 2021 Student Version software. The purpose of this research is to analyze the volume and cost planning using the Building Information Modeling (BIM) 5D concept in structural works, particularly in rebar, concrete, and roof structure works of the Villa construction project on Mulawarman Street, Balikpapan. The method used is to compare the consultant's analysis and BIM analysis. The research results show that the volume with the BIM 5D concept in rebar works is 8.63% smaller than the consultant's analysis, with the BIM 5D concept in concrete works is 9.55% smaller than the consultant's analysis, and with the BIM 5D concept in roof structure works is 64.12% smaller than the consultant's analysis. As for cost calculations, the BIM 5D concept in rebar works is 8.62% smaller than the consultant's analysis, with the BIM 5D concept in concrete works is 9.44% smaller than the consultant's analysis, and with the BIM 5D concept in roof structure works is 64.12% smaller than the consultant's analysis. The conclusion of this research is to identify and evaluate how the use of BIM can affect cost estimation for consultants.